Substantiation of a new technology on purification of axial-flow compressors for gas-turbine plants - Запорожець, О.І.; Савченко, В.І.; Карпенко, С.В. (Proceedings of National Aviation University, 2010)
There was make an analysis of existent methods for cleaning of blades surface for axial-flow compressors of gas-turbine machines. Proposed new method for cleaning of blades surface for axial-flow compressors of gas-turbine machines is based on using of low-temperature ice granules.